2016
DOI: 10.1055/s-0036-1579658
|View full text |Cite
|
Sign up to set email alerts
|

When Aesthetics, Surgery, and Psychology Meet: Aesthetic Nasal Proportions in Patients Having Rhinoplasty and Normal Adults

Abstract: The obsession with facial beauty is not limited to modern culture. Several studies have suggested that facial attractiveness is comparatively independent of culture. AbstractThe aesthetic nasal proportions have played a significant role in rhinoplasty practice. On the other hand, psychological variables also play a crucial role in rhinoplasty. It is of paramount importance for facial plastic surgeons to consider both sides to achieve a more satisfactory outcome. The present study aimed to compare aesthetic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…However, the nose has a special importance because it occupies the central position in the face (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, the nose has a special importance because it occupies the central position in the face (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, the nose has a special importance because it occupies the central position in the face. 12 One of the most important parameters in the nose to measure, is tip rotation.…”
Section: Introductionmentioning
confidence: 99%
“…An arbitrary range of 90 to 115 degrees for the nasolabial angle (in connection with the nasal tip rotation) is common. 12 By measuring this parameter, the far and near obtained number in various researches from the ideal proportion can be identified, and the role of this parameter in assessing postoperative can be assessed. Assessment of some used parameters in facial surgeries and harmony of various facial features are essential to surgeon, who requires facial analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Cosmetic surgery is characterized as a voluntary medical procedure, not always justified by a flagrant aesthetic imperfection, but sometimes by a highly subjective psychological disturbance. For example, Naraghi et al 1 recently demonstrated some psychological factors could be more significant than aesthetic proportions in undergoing facial plastic surgery. Nonetheless, can cosmetic surgery still constitute an adapted response to the patient's psychological suffering?…”
Section: Introductionmentioning
confidence: 99%